Evaluation categories in the criminal law of the Republic of Kazakhstan - Seitzhanova, N.K.; Penchukov, E.V. (Opción, 2019)
Present article analyses such legal phenomenon as evaluation categories, determines its importance in law in general and in criminal law in particular. The research was based on the general academic dialectical method of cognition, which involves the study of legal concepts in their development and interdependence. As a result, in assessing the categories of circumstances precluding the criminality of the act, the opinion of the subject of criminal law is also taken into account. In conclusion, the evaluation categories in criminal law are the norms of the concept (lexical units) used in drafting the norms.